2016
DOI: 10.1016/j.ebiom.2016.02.022
|View full text |Cite
|
Sign up to set email alerts
|

An Eighteen-Gene Classifier Predicts Locoregional Recurrence in Post-Mastectomy Breast Cancer Patients

Abstract: We previously identified 34 genes of interest (GOI) in 2006 to aid the oncologists to determine whether post-mastectomy radiotherapy (PMRT) is indicated for certain patients with breast cancer. At this time, an independent cohort of 135 patients having DNA microarray study available from the primary tumor tissue samples was chosen. Inclusion criteria were 1) mastectomy as the first treatment, 2) pathology stages I-III, 3) any locoregional recurrence (LRR) and 4) no PMRT. After inter-platform data integration o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
33
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(35 citation statements)
references
References 40 publications
(51 reference statements)
1
33
0
Order By: Relevance
“…18-GC development has been reported previously [ 17 ]. Each gene was assigned a weight according to the Cox proportional hazards model to assemble the 18-gene scoring algorithm ( S1 and S2 Tables).…”
Section: Methods and Patientsmentioning
confidence: 70%
See 2 more Smart Citations
“…18-GC development has been reported previously [ 17 ]. Each gene was assigned a weight according to the Cox proportional hazards model to assemble the 18-gene scoring algorithm ( S1 and S2 Tables).…”
Section: Methods and Patientsmentioning
confidence: 70%
“…18-gene score = 4 × TRPV6 + 3 × DDX39 + 8 × BUB1B + CCR1 + STIL + 3 × BLM + 11 × C16ORF7 + 4 × PIM1 + TPX2 + 2 × PTI1 + 2 × TCF3 + CCNB1 + DTX2 + 2 × ENSA + 5 × RCHY1 + 4 × NFATC2IP + OBSL1 + 2 × MMP15 [ 17 ]. We defined patients with scores of ≥21 as high-risk and <21 as low-risk for distant metastasis.…”
Section: Methods and Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…as an 18-gene classifier (18-GC) with more sensitivity, specificity, and accuracy-not only in predicting LRR but also distant recurrence 9,10 . This 18-GC utilises the genes BLM, TCF3, PIM1, RCHY1, PTI1, DDX39, BUB1B, STIL, TPX2, CCNB1, MMP15, CCR1, NFATC2IP, TRPV6, OBSL1, C16ORF7, DTX2, and ENSA, among which 17 were included in the distant genomic model (DGM).…”
mentioning
confidence: 99%
“…In their recent work published in EBioMedicine , Cheng and colleagues developed an 18-gene classifier capable of stratifying breast cancer patients with 0–3 positive lymph nodes (N0–1) after mastectomy into low and high risk groups to better determine the need for post-mastectomy radiation therapy (PMRT)( Cheng et al, 2016 ). Through their work, they found that patients, who were defined by the 18-gene classifier as high risk, had significantly reduced rates of 5-year loco-regional recurrence, distant metastasis-free survival, and overall survival, regardless of lymph node status and breast cancer subtype based on estrogen receptor, progesterone receptor, and human epidermal growth factor receptor 2/neu status.…”
mentioning
confidence: 99%